PENGEMBANGAN SELF-ESTEEM SEBAGAI UPAYA PENINGKATAN KINERJA PENDIDIK DI TKIT 2 QURROTA A’YUN PONOROGO - Ririn Nuraini (IAIN Ponorogo, 2018)
Abstract: This study aims to explain the planning, organizing, implementation, evaluation and impact of self-esteem development in improving educator performance in TKIT 2 Qurrota A'yun Ponorogo. It employed qualitative research design. The result of data analysis showed that self-esteem development process in improving educator's performance in TKIT 2 Qurrota A'yun Ponorogo in accordance with theory of function of planning, organizing, implementation and evaluation of self-esteem development. The development of self-esteem in TKIT 2 Qurrota A'yun Ponorogo has a positive impact in improving the performance of educators as well as supports the development activities of self-development and career of educators. This is in line with the theory of the characteristics of self-esteem development activities and the variables that affect performance.Abstrak: Penelitian ini bertujuan untuk menjelaskan perencanaan, pengorganisasian, pelaksanaan, evaluasi dan dampak pengembangan self-esteem (harga diri) dalam meningkatkan kinerja pendidik di TKIT 2 Qurrota A’yun Ponorogo. Desain penelitian ini adalah kualitatif. Berdasarkan proses pengumpulan dan analisis data, penelitian ini menghasilkan: proses pengembangan self-esteem dalam meningkatkan kinerja pendidik di TKIT 2 Qurrota A’yun Ponorogo sesuai dengan teori fungsi perencanaan, pengorganisasian, pelaksanaan dan evaluasi pengembangan self-esteem. Pengembangan self-esteem di TKIT 2 Qurrota A’yun Ponorogo berdampak positif dalam meningkatkan kinerja pendidik dan juga dapat mengcover kegiatan pengembangan diri maupun pengembangan karir pendidik. Hal ini sesuai dengan teori ciri-ciri kegiatan pengembangan self-esteem dan variabel yang mempengaruhi kinerja.